The Traffic in Babies : Cross-Border Adoption and Baby-Selling between the United States and Canada, 1930-1972 - Balcom, Karen Andrea, 1965- (Book collections on Project MUSE., 2011)
"Karen A. Balcom details the dramatic and sometimes tragic history of cross-border adoptions - from the Ideal Maternity Home case and the Alberta Babies-for-Export scandal to trans-racial adoptions of Aboriginal children. Exploring how and why babies were moved across borders, The Traffic in Babies is a fascinating look at how social workers and other policy makers tried to find the birth mothers, adopted children, and adoptive parents who disappeared into the spaces between child welfare and immigration laws in Canada and the United States."--Pub. desc.